2012
DOI: 10.1016/j.fuel.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the viscoelastic properties of bituminous binders via thiourea-modification

Abstract: Although added in a very low concentration, bitumen controls the final properties and performance of the resulting asphalt mixture. As an alternative to classic bitumen modification with polymers, we herein propose the use of thiourea, which has proved to efficiently enhance the binder thermo-rheological properties in a broad temperature interval. As revealed by thermogravimetric and chemical analysis, benefits above may derive from new structures, probably formed by the interaction between ammonium thiocyanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Eventually, the decrease obtained in the thermal events of the non-reversing heat flow component for both additives provides evidence of lower degrees of molecular ordering in the different bituminous phases, involving a reduction in the crystalline domains, in favor of the amorphous content . In the case of DBSA, it is further accompanied by a decrease in T g1 and T g2 , which translates into improved mechanical performance against fracture at low-to-intermediate temperatures. ,, …”
Section: Results and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Eventually, the decrease obtained in the thermal events of the non-reversing heat flow component for both additives provides evidence of lower degrees of molecular ordering in the different bituminous phases, involving a reduction in the crystalline domains, in favor of the amorphous content . In the case of DBSA, it is further accompanied by a decrease in T g1 and T g2 , which translates into improved mechanical performance against fracture at low-to-intermediate temperatures. ,, …”
Section: Results and Discussionmentioning
confidence: 86%
“…32 In the case of DBSA, it is further accompanied by a decrease in T g1 and T g2 , which translates into improved mechanical performance against fracture at low-to-intermediate temperatures. 30,31,33 3.5. Compositional Characterization.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing concentrations of paraffin wax added to base bitumen, three different effects are noticed: (i) saturate fractions increase significantly, (ii) aromatics and resins decrease progressively, and (iii) asphaltenes remain almost constant. It has been reported that the asphaltene fraction is the most sensitive to change after chemical bitumen modification; however, the chromatographic results indicated that paraffin wax addition significantly affects other families of SARAs compounds since the initial relative proportion of asphaltenes, aromatics, and resins is not conserved. Therefore, it is expected a notable modification of the colloidal arrangement of bitumen compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Cuadri et al [31,32], the bitumen modification route through thiourea is related to adducts derived from the interaction between the asphaltenes and the ammonium thiocyanate (NH4SCN), arising from the melting/thermal decomposition of Th during its mixing with bitumen at 180 ºC. As a result, thiourea and its derivatives containing N-H bonds contribute to enhance the colloidal structure of bitumen by developing a hydrogen-bond network.…”
Section: Rheological Behaviour At High In-service Temperaturesmentioning
confidence: 99%